Resource orchestration in family firms: investigating how entrepreneurial orientation, generational involvement, and participative strategy affect performance - Chirico, Francesco; Sirmon, David G.; Sciascia, Salvatore; Mazzola, Pietro (Strategic Entrepreneurship Journal, 2011)
Abstract Drawing on the process of resource orchestration, we argue a co‐alignment of multiple factors is needed for family firms to increase performance through entrepreneurship. Specifically, we posit that entrepreneurial orientation provides the mobilizing vision to use the heterogeneous yet complementary knowledge and experiences offered by increased generational involvement toward entrepreneurship. However, without a coordinating mechanism, generational involvement leads to conflict and negative outcomes. When, instead, it is also coordinated via a participative strategy, performance gains are achieved. In sum, results suggest that realizing the benefits from entrepreneurship in family firms is a complicated matter affected by the synchronization of entrepreneurial orientation, generational involvement, and participative strategy. Copyright © 2011 Strategic Management Society.